MSC-Derived Extracellular Vesicles against Pulmonary Fibrosis of Rodent Model: A Meta-Analysis - Zhou, Xinghong; Liu, Ya; Xie, Jiahui; Wen, Ziqi; Yang, Jiaqi; Zhang, Hanyue; Zhou, Zijing; Zhang, Jinyu; Cui, Huixian; Ma, Jun (Current Stem Cell Research & Therapy, 2025)
BackgroundPulmonary fibrosis (PF) is a fatal disease distinguished by structural destruction and dysfunction, accompanied by continuous accumulation of fibroblasts, which eventually leads to lung failure. Preclinical studies have shown that the administration of mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) may be a safe and effective treatment for PF. The purpose of our meta-analysis is to evaluate the efficacy of MSC-EVs therapy and identify therapeutic aspects related to PF.MethodsOur study (up to April 6, 2022) identified English and Chinese, preclinical, controlled, and in vivo studies to examine the application of MSC-EVs in the treatment of PF. The risk of bias (ROB) is assessed using the SYRCLE bias risk tool. The primary outcomes include collagen content, α-smooth muscle actin (α-SMA), hydroxyproline (HYP) content, and transforming growth factor-β1 (TGF-β1).ResultsThirteen studies were included in this meta-analysis. Ten studies evaluated the collagen content, five studies evaluated the α-SMA, five studies evaluated the HYP content, and six studies evaluated the TGF-β1. Compared to the control group, MSC-EVs therapy was associated with a significant reduction of collagen accumulation, α-SMA, HYP content, and TGF-β1.ConclusionThe administration of MSC-EVs is beneficial for the treatment of rodent PF models. However, the safety and effectiveness of the application in human PF diseases have yet to be confirmed. The application of MSC-EVs in the treatment of PF needs to be further standardized in terms of source, route of administration, and culture method.
Keywords: preclinical studies